Comparative evaluation of 3D-printed and ACR vials for PET/CT QA: SUV and heterogeneity analysis - Hanafi, M. H.; Mohd Noor, N.; Ramli, S. H.; Ahmad Saad, F. F.; Mohamed, F.; Musarudin, M. (Elsevier, 2025)
This study evaluates the performance of 3D-printed vials as alternatives to standardized American College of Radiology (ACR) phantoms for PET/CT quality assurance using standardized uptake values (SUVmax, SUVmean) and heterogeneity metrics. Four paired ACR vials (25, 16, 12, 8 mm) and 3D-printed vials (matched dimensions, 0.2 mm layer resolution) were imaged on a Siemens Biograph system following clinical protocols. Quantitative analysis revealed excellent agreement for 25 mm vials, with SUVmax values of 2.37 ± 0.02 (ACR) versus 2.39 ± 0.03 (3D-printed) (p > 0.05), both within clinical acceptance criteria (1.8–2.8) per ACR guidelines. The 16 mm/25 mm SUV ratio (0.89 for 3D-printed vs. 0.93 for ACR) exceeded the 0.7 diagnostic threshold, confirming preserved contrast recovery. However, increasing heterogeneity was observed in smaller 3D-printed vials (COV up to 1.39 % vs. 0.95 % for ACR at 25 mm), attributed to material inconsistencies and printing artifacts. These findings demonstrate that 3D-printed vials perform comparably to ACR standards for clinically relevant volumes (≥12 mm) while require further optimization of printing resolution and material selection.